Survival Impact of Ovarian Preservation on Women With Early-Stage Endometrial Cancer: A Systematic Review and Meta-analysis. Issue 1 (1st January 2016) - Gu, Haifeng; Li, Jundong; Gu, Yangkui; Tu, Hua; Zhou, Yun; Liu, Jihong
Abstract : Objective: The aim of this article was to investigate the survival impact of ovarian preservation in surgically treated patients with early-stage endometrial cancer using a meta-analysis. Methods: Major online databases, including PubMed, EMBASE, Web of Science, the Cochrane Library, as well as Grey Literature database, were searched to collect studies on the effects of ovarian preservation compared with bilateral salpingo-oophorectomy (BSO) for surgical treatment in endometrial cancer patients. The literature search was performed up to April 2016. The results were analyzed using RevMan 5.0 software and Stata/SE 12.0 software. Results: Totally, 7 retrospective cohort studies including 1419 patients in ovarian preservation group and 15, 826 patients in BSO group were enrolled. Meta-analysis showed that there was no significant difference in overall survival between the patients treated with ovarian preservation and BSO (hazards ratio [HR], 1.00; 95% confidence interval [CI], 0.72–1.39; P = 1.00). Similar result was achieved in the young and premenopausal women (HR, 0.99; 95% CI, 0.70–1.39; P = 0.39). Furthermore, the disease-free survival of patients whose ovaries were preserved was slightly compromised but with no statistical significance (HR, 1.49; 95% CI, 0.56–3.93; P = 0.42). Conclusions: Ovarian preservation may be safe in patients with early-stage endometrial cancer, and it could be cautiously considered in treating young and premenopausal women because it is not associated with an adverse impact on the patients' survival. Given the inherent limitations of the included studies, further well-designed randomized controlled trial are needed to confirm and update this analysis.